2014
DOI: 10.1149/06408.0069ecst
|View full text |Cite
|
Sign up to set email alerts
|

ALD Grown Rare-Earth High-k Oxides on Ge: Lowering of the Interface Trap Density and EOT Scalability

Abstract: Y2O3 and L2O3/ZrO2 stacks have been examined in terms of their electrical properties in Ge capacitors. It is discussed that scaling of L2O3/ZrO2 stacks into the sub 1 nm EOT regime can be achieved either by using thin amorphous La2O3 capped by a thin ZrO2 layer or by stabilizing the tetragonal or cubic very high-k phase of ZrO2 induced by diffused La and Ge atoms during a PDA step. Y2O3 shows very good interfacial qualities in terms of a low interface trap density and hysteresis when an annealing in O2 atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The Y 2 O 3 and AlYO 3 film thickness was measured as a function of the ALD cycle by ellipsometry. The deposition rate of Y 2 O 3 is estimated to be 0.12 nm/cycle, which is close to the previously reported value, 0.15nm/cycle [12]. Also, the permittivity estimated from the accumulation capacitance is found to be around 13, which is close to the ideal permittivity value of 15 [12] and twice higher than that of Al 2 O 3 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The Y 2 O 3 and AlYO 3 film thickness was measured as a function of the ALD cycle by ellipsometry. The deposition rate of Y 2 O 3 is estimated to be 0.12 nm/cycle, which is close to the previously reported value, 0.15nm/cycle [12]. Also, the permittivity estimated from the accumulation capacitance is found to be around 13, which is close to the ideal permittivity value of 15 [12] and twice higher than that of Al 2 O 3 .…”
Section: Resultssupporting
confidence: 87%
“…The deposition rate of Y 2 O 3 is estimated to be 0.12 nm/cycle, which is close to the previously reported value, 0.15nm/cycle [12]. Also, the permittivity estimated from the accumulation capacitance is found to be around 13, which is close to the ideal permittivity value of 15 [12] and twice higher than that of Al 2 O 3 . On the other hand, the deposition rate of AlYO 3 are estimated as 0.18 nm/unit cycle, where one unit cycle includes one supply cycle of Al(CH 2 ) 3 and one supply cycle of (CpMe) 3 Y.…”
Section: Resultssupporting
confidence: 87%
“…The contribution of the La 2 O 3 interfacial passivation layer to the amount of interface traps at the La 2 O 3 /Ge interface could be explained as follows: during the ALD process of La( i- PrCp) 3 and H 2 O precursors and the high temperature PDA process, La 2 O 3 is more likely to react with outdiffused Ge atoms and Ge oxides nearby the interface to form stable LaGeO x compound. The stable LaGeO x compound could effectively suppress Ge outdiffusion, and further inhibit the decomposition or desorption from GeO 2 to volatile GeO (following the reaction equation of GeO 2 + Ge → 2GeO), contributing to the reduction of structural defects and dangling bonds [31,32]. The D it value (2.71 × 10 12 eV −1 cm −2 ) of sample S4 achieved in our work is comparable with the results obtained in the reported literatures at La 2 O 3 /Ge interfaces of 3 × 10 12 [8] and 3.5 × 10 12 eV −1 cm −2 [25], indicating that a La 2 O 3 passivation layer with 15 ALD cycles (~1.3 nm) can effectively suppress the generation of interface states at high k dielectrics/Ge interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Being a thermally stable germanate compound on the surface of Ge substrate, LaGeO x was reported to be of help in suppressing Ge out-diffusion and improving interface quality. However, among the germanium oxides, GeO is volatile and sublimes leaving behind a defective interface contained lots of defects and dangling bonds, which makes it known to have an adverse influence on the interfacial properties [11]. Additionally, it has been reported that at temperatures of up to 430 °C, GeO 2 becomes unstable, and will react with substrate Ge atoms generating volatile GeO, following the reaction of GeO 2 + Ge → 2GeO [7].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, rare earth oxides have been considered as a promising passivation interlayer for high-k dielectric grown on Ge [9]. Furthermore, La-based dielectric materials have been shown to form a good passivation layer due to the formation of a stable La germanate compound on Ge substrate which could prevent the formation of volatile GeO [10,11]. Among various deposition methods for growing high-k dielectric films, atomic layer deposition (ALD) has been considered as one of the most promising technique to produce high-k dielectric films in high quality due to the outstanding characteristics for precise thickness and composition control, excellent uniformity and process compatibility to conventional CMOS process [12,13].…”
Section: Introductionmentioning
confidence: 99%